City air or city markets: productivity gains in urban areas - Douglas J. Krupka (Institute for the Study of Labor (IZA), 2007)
Persistent productivity gains to rural-urban migrants have been documented by a number of researchers. One interpretation of this result is that individuals learn higher value skills in cities than they would have learned in less dense areas. Another explanation for this result, however, is that thicker urban labor markets allow for better matches, which are realized slowly through a process of subsequent job searches. Surprisingly, there has been no empirical test of these two interpretations to this date. This paper uses NLSY79 geocode data to assess whether wage growth of urban workers is due primarily to time spent in the urban environment (and thus learning), or job changes. The evidence suggests that both these processes are probably at work.
Keywords: R11; 330; Productivity; agglomeration economies; urban wage premium; matching; learning; Städtischer Arbeitsmarkt; Lohnstruktur; Agglomerationseffekt; Matching; Lernprozess; Arbeitsproduktivität; Landflucht; USA